Investigation of Correlations Between Optical Coherence Tomography Biomarkers and Visual Acuity in X-Linked Retinoschisis - Lin, Zhanjie; Zang, Siwen; Maman Lawali, Dan Jouma Amadou; Xiao, Yu; Zeng, Xiaomin; Yu, Honghua; Hu, Yijun (Frontiers in Medicine, 2022)
Purpose: To investigate the imaging biomarkers of spectral-domain optical coherence tomography (SD-OCT) and their correlations with age and best-corrected visual acuity (BCVA) in patients with X-linked retinoschisis (XLRS). Methods: OCT images of 72 eyes of 39 patients with confirmed XLRS were obtained to assess imaging biomarkers, including but not limited to the automatic evaluation of foveal thickness, central subfield thickness (CST), macular volume, and the manual measurement of area of macular schisis cavity (AMS). Correlations between age/BCVA and all OCT parameters were computed as well. Results: In this study, median age was 10.5 (8-12) years old and median BCVA was 0.90 (0.70-1.00) logMAR. Macular retinoschisis was found in all affected eyes, with peripheral retinoschisis (PRS) in 34 (47.2%) eyes. Cystic cavities most frequently affected inner nuclear layer (100%) in the macula. Ellipsoid zone (EZ) defects occurred in 53 (73.6%) eyes. As for correlation, BCVA was significantly correlated with several OCT parameters, including CST, AMS, EZ defect, PRS and vitreomacular adhesion, while no correlation was found between age and any OCT parameter. Conclusion: Explicable OCT imaging biomarkers such as CST, AMS, and photoreceptor defects were identified and may serve as reference parameters or potential regions of interest for future observational and interventional research design and result interpretation.